Innovative Teachers: paradigm shifts based on the needs presented by students (Research, Society and Development, 2020)
This research is the product of a research on innovative practices developed at the Federal Institute of Education, Science and Technology of Ceará (IFCE), methodological innovations gravitate around the use of technologies, gamification, simulation of professional daily life, among other categories. We aim to highlight training processes stimulated by students, based on teachers' speeches that bring together the innovation of pedagogical practices supported by the needs highlighted by students. We base our reflections on the discourse of 19 teachers who claim to have initiated the innovations based on the needs and demands of students, the student being an important and integral part in the process of teaching, learning and teacher training. The analyses were carried out based on microanalysis and as a collection tool the online questionnaire was used, this process was conducted in the light of qualitative research. Significant changes were noted in the spaces and in the construction of actions aimed at moments of lucid learning, close to reality that progressively deconstruct practices disconnected from the contexts of the students.